Domestic market of Arctic Uluses of Sakha (Yakutia) in the Far Eastern Federal District macro area - Lifen, Yang; Fedorov, Yuriy Yu. (Nexo Revista Científica, 2021)
This study reviews and compares the market potential of two macro-areas in the Republic of Sakha (Yakutia) in the AZRF (Arctic zone of the Russian Federation) and the FEFD (Far Eastern Federal District. Moreover, this work shows that a significant part of supply and demand in municipalities' domestic markets is concentrated in the FEFD. Until recently, the AZRF and the FEFD were not considered by the State as a single government body. Transferred powers to the Ministry of the Russian Federation for the development of the Far East and the Arctic has allowed the territory of the Arctic uluses of the Republic of Sakha (Yakutia) to be included in the social and economic development of the FEFD.